Download presentation
Presentation is loading. Please wait.
1
The Proof of unbiased estimator of 2 (Ref. To Gujarati (2003)pp.100-101) The least squares formulas (estimators) in the simple regression case: b2b2 = xiyixi2xiyixi2 = k i (Y i -Y) = k i Y i - Y k i = k i Y Substitute the PRF: Y = 1 + 2 X + u into the b 2 formula b 2 = k i ( 1 + 2 X i + u i ) = 1 k i + 2 k i X i + k i u i = 2 + k i u Since k i = 0 k i X = 1 = 0 = 1 Take the expectation on both side: E(b 2 ) = 2 + k i E( u i ) E(b 2 ) = 2 (unbiased estimator) = 0 By assumptions: E(u i ) = 0 E(u i,u j ) = 0 Var(u I ) = 2 = 0 = k i
2
Var (b 2 ) = E[ b 2 – E(b 2 )] 2 = E[ b 2 - 2 ] 2 = E[ k i u i ]2 = E[k 1 2 u 1 2 + k 2 2 u 2 2 + k 3 2 u 3 2 +….+2k 1 k 2 u 1 u 2 +2k 1 k 3 u 1 u 3 + …..] = k 1 2 E(u 1 2 )+ k 2 2 E(u 2 2 ) + k 3 2 E(u 3 2 ) +….+2k 1 k 2 E(u 1 u 2 ) +2k 1 k 3 E(u 1 u 3 )+….. = k 1 2 2 + k 2 2 2 + k 3 2 2 + …. + 0 + 0 + 0 + … = 2 k i 2 = 2 (x i / x i 2 ) 2 = 2 x i 2 / ( x i 2 ) 2 = 2 / x i 2 By assumptions: E( i ) = 0 E( i, j ) = 0 Var( I ) = 2 = 0 E(b 1 ) = 1 (unbiased estimator) The Proof of variance of 2 (Ref. To Gujarati (2003)pp.101-102) ^
3
By definition: Cov (b 1, b 2 ) = E{[b 1 - E(b 1 )][b 2 - E(b 2 )]} = E{[(Y – b 2 X) – (Y - 2 X)][b 2 - 2 ]} = E{[-X(b 2 - 2 )][b 2 - 2 ]} = -X E(b 2 - 2 ) 2 = -X[ 2 / x i 2 ] The Proof of covariance of 1 and 2 : cov( 1, 2 ) ^ ^ ^ ^ (Ref. To Gujarati (2003)pp.102)
4
The OLS estimator of 2 is: b 2 = = k i Y i xiyixi2xiyixi2 Now suppose an other linear estimator of 2 is b 2 * = w i Y i And assume w i k i Since b 2 * = w i Y i = w i ( 2 + 2 X i +u i ) = w i 1 + 2 w i X i + w i u I Take the expectation of b 2 * : E( b 2 * ) = E( w i 1 )+ 2 E( w i X i )+ E( w i u i ) = 1 w i + 2 w i X i since E(u i )=0 For b 2 * to be unbiased, i.e., E(b 2 * ) = 2 there must be w i =0, and w i X i = 1 The Proof of minimum variance property of OLS (Ref. To Gujarati (2003)pp.104-105)
5
And the variance of b 2 * is: Var(b 2 *) = E[b 2 * - E(b 2 * )] 2 = E[ b 2 * - 2 ] 2 = E( w i u i ) 2 = w i 2 E(u i ) 2 = 2 w i 2 = 2 [(w i - k i ) + k i )] 2 = 2 (w i - k i ) 2 + 2 k i 2 + 2 2 (w i - k i )k i = 2 (w i - k i )2 + 2 k i 2 Since k i =0 = 2 (w i - k i )2 + 2 / x i 2 = 2 (w i - k i )2 + Var(b 2 ) Therefore, only if w i = k i, then Var(b 2 * ) = Var(b 2 ), Hence the OLS estimator b 2 is the min. variance. If it is not min.=>OLS isn’t the best = 0 If b 2 * is an unbiased estimator, then b 2 * = w i Y i = w i ( 1 + 2 X i +u i ) = 2 + w i u i Therefore, (b 2 * - 2 ) = w i u i
6
The Proof of unbiased estimator of 2 Var( u ) = E(u 2 ) = 2 ^ ^ ^ Or Var( e ) = E(e 2 ) = 2 Since Y = 1 + 2 X + u and Y = 1 + 2 X + u => y = 2 x + (u - u ) e = Y – b 1 – b 2 X and 0 = Y – b 1 – b 2 X => e = y – b 2 x e = 2 x + (u - u ) – b 2 x = ( 2 – b 2 )x + (u - u ) Deviation form Take squares and summing on both sides: e 2 = ( 2 –b 2 ) 2 x 2 + (u - u ) 2 – 2( 2 –b 2 ) x(u - u) Take expectation on both sides: E( e 2 ) = E[( 2 –b 2 ) 2 ] x 2 + E[ (u - u ) 2 ] – 2E[( 2 –b 2 ) x(u - u)] I II III (Ref. To Gujarati (2003)pp.102-03)
7
Utilize the OLS assumptions, that are E(u) = 0, E(u 2 ) = 2 and E(u i u j ) = 0 And get I = 2 II = (n-1) 2 III = -2 2 Substituting these three terms, I, II, and III into the equation and get E( e 2 ) = (n-2) 2 And if define 2 = e 2 /(n-2) Therefore, the expected value is E( 2 ) = E( e 2 )/(n-2) = (n-2) 2 /(n-2) = 2 ^ ^
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.